A New Structural Technique for Examining Ion-Neutral Association in Aqueous Solution - Mason, Philip E. (2013)
The method of intramolecular coordination number concentration invariance (ICNCI) is used on neutron diffraction with isotopic substitution (NDIS) measurements of aqueous solutions to separate the intra- and intermolecular contributions to the total intensities. Molecular dynamics simulations of corresponding systems are then used to interpret the ICNCI function. It is found that the ICNCI function (characterized by two concentration measurements) is sensitive specifically to intermolecular association and that the molecular dynamics can successfully replicate this function in the cases of the neutral species xylose and pyridine in aqueous solution. ICNCI functions can also be obtained by the addition of a cosolute (such as adding GdmCl or Gdm(2)SO(4) to pyridine solutions). In that case it is found that molecular dynamics can replicate the ICNCI function for the addition of GdmCl to pyridine, but fails to successfully replicate the same function for the addition of Gdm(2)SO(4). This result implies that the interaction of pyridine with guanidinium sulfate is over-estimated in MD these simulations, and is of significant importance to the use of molecular dynamics simulations to elucidate an atomic level understanding of the Hofmeister series.